2005
DOI: 10.1111/j.1527-5299.2005.03722.x
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor Is Overexpressed in Cardiomyocytes of Patients With Congestive Heart Failure

Abstract: Mineralocorticoid receptors (MRs) have been identified in the human cardiovascular tissues. We determined MR expression in the failing heart to clarify the mechanism of action of aldosterone antagonist in the treatment of congestive heart failure. MR protein and MR mRNA content were detected by immunohistochemical staining and in situ hybridization in the cardiac tissues. Immunohistochemical staining of the receptor, as well as in situ hybridization of MR mRNA, was dense in cardiomyocytes of the failing left v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…This is particularly important for the failing heart in which the mineralocorticoid receptor is overexpressed. 3 Indeed, immunohistochemical staining of the receptor was dense in the cytoplasm of the myocytes of the failing heart compared with controls. 3 Interestingly, eplerenone had a similar effect on the pump current density when administered, in vitro, to myocytes from animals not treated chronically with eplerenone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly important for the failing heart in which the mineralocorticoid receptor is overexpressed. 3 Indeed, immunohistochemical staining of the receptor was dense in the cytoplasm of the myocytes of the failing heart compared with controls. 3 Interestingly, eplerenone had a similar effect on the pump current density when administered, in vitro, to myocytes from animals not treated chronically with eplerenone.…”
Section: Discussionmentioning
confidence: 99%
“…3 Indeed, immunohistochemical staining of the receptor was dense in the cytoplasm of the myocytes of the failing heart compared with controls. 3 Interestingly, eplerenone had a similar effect on the pump current density when administered, in vitro, to myocytes from animals not treated chronically with eplerenone. Further studies will be needed to clarify the detailed mechanisms by which eplerenone activates the sodium-potassium pump.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Aldo and sodium load have been reported to cause inflammation and fibrosis in the cardiovascular system. 8,9 However, because the heart and the vasculature do not have enough expression of 11b-hydroxysteroid dehydrogenase type 2, 10 the precise mechanism of how Aldo binds MR and expresses its pro-inflammatory action without glucocorticoid deactivation has not yet been elucidated. Osteopontin (OPN), which is an acidic glycoprotein of B300 amino acids, was first described after it was isolated from bovine bone matrix.…”
Section: Introductionmentioning
confidence: 99%
“…5 RALES 6 and EPHESUS 7 have demonstrated that the addition of MR antagonists to optimal medical therapy substantially reduces the risk of both morbidity and mortality among patients with severe heart failure or acute myocardial infarction complicated by left ventricular dysfunction and heart failure. The RAAS activation in AF is similar to that in heart failure; it can therefore be hypothesized that the expression of MR in patients with AF may change.…”
Section: Introductionmentioning
confidence: 99%